A Família do tesouro: a monumentalização da família Albuquerque Maranhão e a luta pelo poder no Rio Grande do Norte (1889-1914) - Costa, Helensandra Lima da (2013)
The objective of this study is to discuss the process of building a family monumentalization Albuquerque Maranhão showed that both the traditional historiography of Rio Grande do Norte, represented by Tavares de Lyra, Rocha Pombo e Câmara Cascudo, as reflected in urban areas of Natal. To understand this process, we intend to analyze the production of the aforementioned authors as well as more recent studies, trying to discern or identify an attempt to link them to the family name to the history of Albuquerque Maranhão State, which ended up giving visibility to this group, making it the characters featured in the scenario of local history, investing them with a monumental character. In addition to historical analysis, we observe changes in the urban landscape of the city of Natal in the early twentieth century orchestrated by members of this family, which tied his line to public spaces for a new and modern city. Through this review, we will be able to realize that such practices turned out to be a stage of political disputes between Albuquerque Maranhão and opposition groups who were anxious to remove them both from the center of historical narratives on the Rio Grande do Norte, as well as the political space of the State environment exclusive domain of this group for nearly twenty years